Ruthenium-Catalyzed Asymmetric Dehydrative Allylic Cyclization of Five-Membered Chalcogen Heteroaromatics - Tanaka, Shinji; Iwase, Shoutaro; Kanda, Sena; Kato, Marie; Kiriyama, Yutaro; Kitamura, Masato (Synthesis, 2021)
The asymmetric dehydrative intramolecular allylation reactions of furan and thiophene were performed using a cationic cyclopentadienyl-ruthenium (CpRu) complex of a chiral pyridine carboxylic acid, namely Cl-Naph-PyCOOH. Both furan and thiophene tethered with an allylic alcohol gave the corresponding bicyclic compounds in high yields and enantioselectivities using 0.1–5 mol% of the catalyst. The reaction was found to proceed via a similar enantioface selection mechanism to that previously reported by our group, which involved halogen and hydrogen bond formation, in addition to the generation of an intermediate σ-allyl complex.
Keywords: furan; thiophene; dehydrative allylation; ruthenium; asymmetric reaction